1967
DOI: 10.1111/j.1467-6494.1967.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Balancing and extremity effects in reactions of receiver to source and content of communications1

Abstract: This study is one of a senes designed to mvestigate the imphcations of a stmctural balance model of communication effects (Feather, 1964(Feather, , 1967a This model uses the mathematical theory of lmear graphs to represent the basic communication situation m which a source (S) is presenting a commumcation (C) about an issue (I) to a receiver (R) These four elements of the communication situation are mapped mto pomts of a lmear graph, and attitiidmal and unit relations between the elements are mapped mto lmes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1967
1967
1982
1982

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In some studies this emerges as a main effect: in pleasantness ratings (77,78,196) , expectations about change (47) , and learning (265)(266)(267). In some studies this emerges as a main effect: in pleasantness ratings (77,78,196) , expectations about change (47) , and learning (265)(266)(267).…”
Section: Balance Theorymentioning
confidence: 98%
“…In some studies this emerges as a main effect: in pleasantness ratings (77,78,196) , expectations about change (47) , and learning (265)(266)(267). In some studies this emerges as a main effect: in pleasantness ratings (77,78,196) , expectations about change (47) , and learning (265)(266)(267).…”
Section: Balance Theorymentioning
confidence: 98%
“…Predictions about the strength of relations in tnads were based upon a discrepancy principle descnbed in recent publications (Feather, 1966, 1967b, Feather & JefFnes, 1967 In essence this principle states that when two relations m a tnad are of the same sign the third relation will be positive (by the balance principle) and will be stronger as the discrepancy between the two relations decreases When two relations in a tnad are of opposite sign the third relation will be negative (by the balance principle) and will be stronger as the discrepancy between the two relations increases That is, relations of the same sign that are close together in strength are associated with a strong positive third relation within a tnad, relations of diflFerent sign that are far apart in strength are associated with a strong negative third relation within a triad When applied to the structures in Figure 1 this principle would imply, for example, that given s-digraph c and considermg the R-I-C tnad, one would predict a strong negative R -» C attitudinal relation when R -^ I and C -»I are both strong, a moderately negative R ->^ C attitudinal relation when one of the R -»I and C -* I attitudmal relations is strong and the other moderate, and a relatively weak negative R -» C attitudinal relation when R ^ I and C -* I are both moderate m strength When the S-I-C tnad is considered m s-digraph c, one would predict a strong positive S -» C attitudmal relation when S -^ I and C -> I are either both strong or both moderate, and a relatively weak positive S->C attitudmal relation when one of the S-»I and C^I attitudmal relations is strong and the other moderate m strength Similar predictions were made for other triads represented in Figure 1 usmg the discrepancy pnnciple…”
Section: Strength Of Relationsmentioning
confidence: 99%
“…The main efiEect of Commuiucabon Stand on credibility ratmgs was significant in the related study(Feather & Jeffnes, 1967), but in that study no information was given to subjects about the attitude of the source toward the…”
mentioning
confidence: 98%
“…Feather and Jeffries (1967) found that a source must present a positive communication to be perceived as credible by subjects with positive attitudes.…”
mentioning
confidence: 97%
“…Feather and Jeffries (1967) found that a source must present a positive communication to be perceived as credible by subjects with positive attitudes. Osgood and Tannenbaum (1955) proposed an interaction between receiver attitude and the situation conveyed (message) in their conceptualization of incredulity as a function of the amount of incongruity present.…”
mentioning
confidence: 97%